2021
DOI: 10.3390/nu13113751
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Growth Factors and Their Role in NEC Prevention: A Narrative Review

Abstract: Growing evidence demonstrates human milk’s protective effect against necrotizing enterocolitis (NEC). Human milk derives these properties from biologically active compounds that influence intestinal growth, barrier function, microvascular development, and immunological maturation. Among these protective compounds are growth factors that are secreted into milk with relatively high concentrations during the early postnatal period, when newborns are most susceptible to NEC. This paper reviews the current knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 121 publications
0
10
0
1
Order By: Relevance
“…Importantly, Holder pasteurization, which is commonly used for the treatment of donor breast milk, does not reduce EGF concentration. EGF has also been found to play an important role in neonatal disease 49,50 . VEGF, a growth factor, is present in human milk at a much higher concentration than in human serum, 51 and a growing body of literature suggests that it may contribute to pulmonary hypertension, which is usually associated with bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Holder pasteurization, which is commonly used for the treatment of donor breast milk, does not reduce EGF concentration. EGF has also been found to play an important role in neonatal disease 49,50 . VEGF, a growth factor, is present in human milk at a much higher concentration than in human serum, 51 and a growing body of literature suggests that it may contribute to pulmonary hypertension, which is usually associated with bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…EGF has also been found to play an important role in neonatal disease. 49 , 50 VEGF, a growth factor, is present in human milk at a much higher concentration than in human serum, 51 and a growing body of literature suggests that it may contribute to pulmonary hypertension, which is usually associated with bronchopulmonary dysplasia. Our KEGG Pathway analysis also showed that VEGF signalling pathway was significant involved, and our research group will continue to conduct in‐depth exploration on VEGF in the later stage.…”
Section: Discussionmentioning
confidence: 99%
“…Their effect varies between direct effects on breast and milk production, while others may contribute to the growth and differentiation of an infant ‘s tissue ( 6 , 7 , 22 ). The growth factors mainly influence the growth and development of the gastrointestinal tract but may affect glucose metabolism and newborn growth ( 26 , 40 ). However, the differences in the presence of growth factors in the colostrum from mothers with gestational diseases are rare in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing enterocolitis (NEC), an acute inflammatory disease, is one of the most severe gastrointestinal diseases in premature infants and develops in up to 10% of premature infants [63]. Human milk has been proved to reduce the risk of NEC [64,65]. Several in vivo and in vitro studies showed the potential of MDEVs to modulate NEC [37 ▪ ,66 ▪ ,67–69,].…”
Section: Milk-derived Extracellular Vesicle Contentmentioning
confidence: 99%